Rethinking the researcher-researched relationship - Lauren Eva Dyll; Keyan Tomaselli (Communicare)
This article critically examines the conventional researcher-researched relationship that empowers the researcher over the researched. The orthodoxy of objectivity – claimed to locate the researchers as neutral observer – is here argued to be a power relation that has an excluding effect where subject communities are concerned. By means of an archaeological case study that included mapping and interpretation of ancient rock engravings we offer a new way of negotiating interpretations. This new way involved four members from a Bushman community who helped us navigate spiritual, ontological and environmental dimensions in making sense of rock art.